Environmental and social assessments of an Island Marine Park in Malaysia - Mohd Noor, Mohd Iqbal (2018)
This study addresses issues and constraints faced by managing tourism development inside Marine Protected Areas in Malaysia by focusing on Tioman Island Marine Park as case study sites. With increasing number of tourist arrivals and greater tourism development in the area, issues of sustainability of Tioman Island Marine Park might be put into questions. The conflict between tourism development and environmental sustainability in Malaysia Marine Parks is getting complicated when some tourism stakeholders believe that the governing policy of the parks are not tailored for their demands to achieve competitive advantage and this might burden the management of protected areas. This problem is addressed by applying three essays that cover three objectives. The general objective of this study is to assess tourism impact on environment and social behaviour in Tioman Island Marine Parks. The first essay assesses the impact of tourism activities in Tioman Island Marine Park by using Life Cycle Assessment theory. The results of each assessment case indicated that transportation to/from the island, accommodation, snorkeling act ivities, and waterfall trekking activities leave negative impacts on human health, ecosystem quality and resources. The advantages of Life Cycle Assessment method include it offers a rational and comprehensive approach to evaluate the environmental impacts in every stage of a product's system. The second essays purpose is to reveal the current social network of stakeholders, interests, and participation in marine protected areas by applying Social Network Analysis. The study site covers three villages in Tioman Island Marine Park, Malaysia and the stakeholders are representatives from tourism distribution channel of Tioman Island Marine Park. The social network study focused on the discrete ties patterns for these villages and how these patterns can be used to manage the tourism network for the island. Network maps can help policy makers and implementing agency in planning and monitoring changes in tourism suppliers’ arrangements by providing a unique methodological frame for collecting and organizing data. Finally, the third essays aim to investigate the relationship between social capital dimensions and environmental behavior in marine parks and to examine the impact of cultural capital in mediating the relationship between social capital and environmental behavior. Data for this study were gathered from 124 respondents from the tourism distribution channel of Tioman Island Marine Park. The overall research process took over a year, in the month of May to August 2015 and June to August in 2016. The findings revealed positive effects of social capital and cultural capital on environmental behavior. The combination of these three essays proves that tourism development has different impacts on Marine Protected Areas management and its implementation. The research findings could help the government and policy planners by offering important inputs for policy direction in reviewing and analysing the possible impact of existing policies on Marine Park conservation. The contribution of this study in shaping the future of society depends on how policymakers, intellectuals, economic agents, and citizens will decide to orient research and use its results.